Parents Views of Students on Islamic Education Learning at Home During Covid-19 Pandemic Period in Kecamatan Medan Marelan - Abdillah Abdillah; Masganti Masganti; Saddam Husein Siregar (Budapest International Research and Critics University, 2021)
This study took 4 Islamic Religious Education teachers and 3 parents of students to convey their views on learning Islamic Religious Education at home during this pandemic. This study used qualitative research methods. It can be concluded in this study that learning Islamic Religious Education at home is considered less effective. Parents and teachers agree that studying at home is less effective, where teachers have difficulty evaluating and cannot understand students' abilities. Parents have limited ability and time to accompany learning. And students are not disciplined in learning so they play more than learn. The solution offered in this study is for parents and teachers to work together by opening a meeting via WhatsApp group or video conference to discuss what teachers and parents hope to achieve with the school as well, of course. As well as for local governments that are sustainable with the Education Office and Schools to work together to implement health protocols for students and teachers so that learning can be carried out face-to-face by reducing the number of students in the class and maintaining distance or making learning shifts. Even though with a short time getting the material, this is even more beneficial than studying at home As well as for local governments that are sustainable with the Education Office and Schools to work together to implement health protocols for students and teachers so that learning can be carried out face-to-face by reducing the number of students in the class and maintaining distance or making learning shifts.